ChemInform Abstract: Synthesis and Electrochemical Properties of Li(Fe0.5Co0.5)BO3. Issue 46 (November 2015) - Le Roux, Barbara; Bourbon, Carole; Colin, Jean‐Francois; Pralong, Valerie
Abstract The new title compound is prepared by a multiple‐step process involving the preparation of the precursors Fe2B2O5 (I) and Co3(BO3)2 (II) which then are mixed with Li2CO3 and H3BO3 and heated under Ar (500 °C, 1.5 h).